Performance analysis of multi-carrier DS-CDMA wireless communication systems - Amin, Saimoon Ara; Alam, Md. Mahbubul (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2009.